Perkembangan Pertunjukan Wayang Beber Kontemporer Di Era Modernisasi - Muhammad Nur Hariyadi; Narsen Afatara; Agus Purwantoro (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2018)
Research discussed regarding the development of contemporary puppet some in a society now. A puppet beber contemporary some years previously had broken by giving alternative forms of a new and exhibited more simple but is interesting, Shorter performances , and use just taken a figure from real life now. The story delivered also adopt issues is in vogue in the days of the modernization of right now. The puppet beber is one of cultural heritage in Indonesia. A puppet beber some which was a live used for events great kraton, the event ruwatan, clean village, healing the sick, and important event specified java. Now puppet classical considered rarely staged and slightly experienced various a setback in terms of staging, because some years previously had broken puppet classic staged as a means of ritual and rarely staged important as entertainment for the urban nowadays. The puppet beber contemporary appear in order to provide new perspective, so people know back puppet show some years previously had broken who became inherited from an ancestor java.